2019
DOI: 10.1029/2018jg004924
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Seasonal Variations Between Phytoplankton Chlorophyll a and Production in the East China Sea

Abstract: Phytoplankton chlorophyll a (Chla), primary production (PP), and nutrient uptake rates are fundamental and important parameters in marine biogeochemical studies. However, the relationships between them are associated with much uncertainty that reflects gaps in basic understanding of ecosystem dynamic. In this study, we simultaneously measured PP and nitrate assimilation (NA) along with estimated concentrations of nutrients, particulate organic carbon concentrations, phytoplankton Chla, pigments, and carbon bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…These primary production estimations all fall into the range reported by Liu et al. (2019) in ECS (i.e., 87–5,327, 167–3,710, and 92–1,005, mg C/(m 2 day) for May–June, August, and November–December, respectively).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These primary production estimations all fall into the range reported by Liu et al. (2019) in ECS (i.e., 87–5,327, 167–3,710, and 92–1,005, mg C/(m 2 day) for May–June, August, and November–December, respectively).…”
Section: Discussionsupporting
confidence: 79%
“…The parameter of chlorophyll‐ a concentration has long been regarded as an index to evaluate phytoplankton biomass, primary productivity, and trophic conditions in estuarine, coastal, and other marine waters (e.g., Boyer et al., 2009). Interactions and relationships among parameters such as nutrient concentrations and their uptake rates, chlorophyll‐ a concentrations, and mechanisms for bloom events have long been of interest in marine biogeochemical studies (Bode et al., 2005; Dugdale et al., 2007; Heil et al., 2014; Liu et al., 2019; Medina‐Gómez et al., 2019; Nausch et al., 2012; Rees et al., 1999; Vaz et al., 2019). However, whether high nutrient uptake rates result in the high chlorophyll‐ a content or whether the high chlorophyll‐ a level results in high nutrient uptake remains a contentious topic (e.g., Liu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Colijn et al (1990) reported a positive linear correlation (r 2 = 0.81) between MVChl a and primary production within the euphotic layer in the German Bight. Liu X et al (2019) observed that surface MVChl a concentrations had a significantly positive correlation (Spearman, r = 0.41, p<0.01) with integrated primary production in the East China Sea. These previous results imply that photosynthetic pigments may be involved in the production activity of phytoplankton via light energy absorption.…”
Section: Vertical Distribution Characteristics Of Primary Production ...mentioning
confidence: 89%
“…The contribution of biological consumption to the nutrient reduction was estimated by the ratio of Chl to C (Chl/C) and the Redfield stoichiometry. The Chl concentration in this region was 2.0-4.0 µg L −1 , yielding a phytoplankton carbon biomass of 6.0-12.0 µM based on a Chl/C ratio of 30 for the Changjiang plume water in summer (Liu et al, 2019). The estimated consumption of DIN and DIP from the Redfield stoichiometry (106:16:1 for C:N:P) was, respectively, 0.91-1.81 and 0.06-0.11 µM, much smaller than the observed reduction in DIN and DIP in this strongly stratified zone.…”
Section: The Relative Importance Of Mixing and Biological Consumptionmentioning
confidence: 93%